Dissatisfaction with current integration reforms of health insurance schemes in China: are they a success and what matters?. Issue 3 (6th January 2018) - Shan, Linghan; Zhao, Miaomiao; Ning, Ning; Hao, Yanhua; Li, Ye; Liang, Libo; Kang, Zheng; Sun, Hong; Ding, Ding; Liu, Baohua; Liang, Chao; Yu, Miao; et al.
Abstract: Integration reforms have been piloted as key policies to address the fragmented health insurance system in China. They are also regarded as a better choice for realizing a Universal Basic Medical Insurance System (UBMIS). This study has attempted to explore the determinants that may affect respondents' dissatisfaction with the reforms. The aim is to provide evidence for more effective policy adjustment during the next round of nationwide integration reforms in China. A cross-sectional questionnaire survey was conducted in Ningbo, Chongqing and Heilongjiang from 2014 to 2015. A stratified cluster sampling method was adopted. A total of 1644 respondents, working in units related to health insurance, were selected. A multivariate logistic regression model was employed to identify any association between dissatisfaction and the features of the ongoing integration reforms of health insurance schemes. Overall, about 47.6% of the respondents reported dissatisfaction with the ongoing integration reforms. This high level of dissatisfaction was found to be associated with ineffective outcomes of the integration reforms in achieving management system improvement [odds ratio (OR) = 1.846], inequity reduction (OR = 1.464) and actual coverage expansion (OR = 1.350), as perceived by the respondents. Those who were satisfied with the previously separated health insurance schemes (OR = 0.643), and those who preferred other policy options for achieving a UBMIS (OR = 1.471) were more likely to report dissatisfaction with the current reforms. Higher expectations of the risk-pooling level (with ORs ranging from 1.361 to 1.661) also significantly contributed to dissatisfaction. Health insurance managers in China have conflicting opinions about the performance of piloted integration reforms. Many believe that these reforms have failed significantly to improve the management systems, narrow inequity and expand actual benefit coverage. Various strategies should be undertaken in order to address these issues, such as clarifying the administrative institution behind the merged schemes at the central level, unifying the insurance information network, developing consistent policies and bridging the differences in benefits among schemes and regions.